3As in inpatient smoking cessation - Abeela Kanwal Awan; Burhan Khan (Future Healthcare Journal)
Background: Tobacco smoking remains the single biggest cause of preventable and premature death and disability in the UK. Offering advice and assistance for tobacco abstinence in hospitals is a critical aspect of improving overall health and undoubtedly the single most cost-effective strategy that can be employed in the NHS1. Every healthcare encounter serves as an opportunity to Ask, Advise and Assist (3As) patients to quit smoking2. In hospitalised patients, addressing tobacco use presents an invaluable opportunity to initiate and support successful quitting journeys1. Objective: This study aims to determine the prevalence of smoking amongst patients hospitalised in a DGH and to assess the utilisation of the 3As 3,4. Methodology: Cross-sectional survey on 06 occasions across 04 Medical wards of all patients admitted to hospital.These patients were interviewed and data captured directly onto a survey form by the interviewer.Case notes were reviewed to corroborate details. Results: 614 patients were surveyed, but only 532 were able to participate; Male:Female 298:234. (Fig 1) 6.95% of this cohort were smokers, but 100% of them were asked if they smoked, were advised to stop smoking and were assisted in smoking cessation. In contrast, 2.81% of this cohort were currently vaping, and though their vaping status was identified in 100% of the time, no furtheradvice or assistance was offered. (Table 1) Conclusion: Preliminary findings suggest excellent utilisation of the 3As in promoting smoking cessation amongst patients hospitalised. Successful outcomes were associated with the combination of pharmacotherapy, counselling, and ongoing support. Improved patient engagement and satisfaction were observed, with participants expressing gratitude for the hospital's commitment to their overall well-being.This is in marked contrast to similar surveys done in the Outpatient settings in the same hospital in 2011:Smoking prevalence 53/204 (26%); Asked 26/53 (49%); Advised 10/26 (38.5%); Assisted 06/10 (60%)and again in 2019: Smoking prevalence 103/505 (20%); Asked 67/103 (65%); Advised 40/67 (59%);Assisted 15/67 (22%) 5, 6.Hospitalised patients represent a captive audience for smoking cessation interventions when their concern for their health is paramount. A systematic approach to identify, advise and assist smoking cessation results in a holistic attitude combining pharmacological support and referral for counselling and yields potentially promising results. The integration of such programmes into routine hospital care can contribute to improved patient outcomes and long-term reductions in tobacco use.